2022
DOI: 10.1159/000522110
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Subretinal Injection Pressure Prevents Damage in Pigs

Abstract: Introduction Administration of retinal gene- and stem cell therapy in patients with retinal degenerative diseases (RDD) is in many cases dependent of a subretinal approach. It has been indicated that manual subretinal injection is associated with outer retinal damage, which may be explained be high flow rate in the injection cannula. In the present porcine study, we evaluated flow-related retinal damage after controlled subretinal injection at different flow rates. Methods Flow rate through a 41G cannula was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“… 3 , 13 Increased injection pressures have been known to cause atrophy at the injection site in both monkeys 14 and pigs. 15 , 16 Therefore, many gene therapy treatment centers try to minimize injection pressures through the use of injection systems with pneumatic-assisted foot pedals. 17 Although spontaneous enlargement of mechanical RPE defects is not unheard of (e.g., in myopes), this type of mechanical atrophy would be presumed to be mostly stationary or self-limiting 14 rather than progressive and be present in both sham and AAV-treated groups.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 13 Increased injection pressures have been known to cause atrophy at the injection site in both monkeys 14 and pigs. 15 , 16 Therefore, many gene therapy treatment centers try to minimize injection pressures through the use of injection systems with pneumatic-assisted foot pedals. 17 Although spontaneous enlargement of mechanical RPE defects is not unheard of (e.g., in myopes), this type of mechanical atrophy would be presumed to be mostly stationary or self-limiting 14 rather than progressive and be present in both sham and AAV-treated groups.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the optimal injection pressure is crucial for the safety of this technique as both low and high injection pressure may be associated with mechanical RPE/retinal damage due to a prolonged permanence of the needle in the subretinal space and the high flow generated, respectively [ 22 ]. In this regard, a recent study on porcine eyes in vivo reported that injection pressure up to 24 psi might be safe, resulting in minimal retinal damage and no functional changes on the multifocal electroretinogram [ 22 ]. To note, the injection pressure to initiate the bleb formation is higher than that required for the bleb propagation [ 21 ].…”
Section: Subretinal Injection For Gene Therapymentioning
confidence: 99%
“…For CRAO/CRVO or submacular hemorrhage caused by AMD, the intra-vascular injection of tissue plasminogen activator solution (tPA) or subretinal injection of air and tPA has emerged as a new therapeutic approach [5,6]. Subretinal drug delivery involves directly injecting the drug into the subretinal space, allowing the drug to directly act on the retina and retinal pigment epithelium (RPE) [7]. For intra-vascular injection in retinal artery cannulation and retinal vein cannulation, the surgeons inject thrombolytic drugs into the occluded retinal arteries or veins to lyse the thrombus, thereby restoring blood circulation to the retinal vessels [8,9].…”
Section: Introductionmentioning
confidence: 99%